A mathematical model for entropy generation in a Powell-Eyring nanofluid flow in a porous channel. Issue 5 (May 2019) - Ogunseye, Hammed Abiodun; Sibanda, Precious
Abstract: The continuous generation of entropy leads to exergy destruction which reduces the performance of a physical system. Hence, entropy minimization becomes necessary. New applications of nanofluids due to their enhanced thermo-physical properties has spurred new studies into the heat transfer and entropy generation rate in nanofluids in the last decade. In this study, we investigate the heat transfer performance and entropy generation rate in a mixed convective flow of a hydromagnetic Aluminum oxide-water Powell-Eyring nanofluid flow through a vertical channel. The nanofluid dynamic viscosity adopted is based on experimental data. The combined effects of the magnetic field, nonlinear thermal radiation, viscous dissipation, suction/injection and convective cooling on the heat transfer and entropy generation were considered. The dimensionless equations describing the flow and energy balance were solved using an efficient iterative spectral local linearization method. The computational analysis of the rate of entropy generation in the channel for various flow parameters is presented. The result shows that increasing the nanoparticle volume fraction and thermal radiation parameter enhanced the temperature profiles, entropy generation and the Bejan number. The results from this study may help engineers in the optimization of thermal systems.